2019
DOI: 10.1021/acs.jpcc.9b02625
|View full text |Cite
|
Sign up to set email alerts
|

Sulfolane-Based Highly Concentrated Electrolytes of Lithium Bis(trifluoromethanesulfonyl)amide: Ionic Transport, Li-Ion Coordination, and Li–S Battery Performance

Abstract: Following our recent study demonstrating predominant Li-ion hopping conduction in sulfolane (SL)-based highly concentrated electrolytes with LiBF4, LiClO4, and lithium bis­(fluorosulfonyl)­amide, herein a systematic study on transport properties and Li-ion coordination of SL-based electrolytes with lithium bis­(trifluoromethanesulfonyl)­amide was performed. In the highly concentrated region, Li ions clearly diffuse faster than SL and TFSA anions. The two oxygen atoms of the SL sulfonyl group tend to coordinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
270
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(290 citation statements)
references
References 61 publications
7
270
0
Order By: Relevance
“…However, the formation of aggregate species seems to have a rather different influence on the transport of Li + ions. It has been proposed that, in a concentrated electrolyte, the Li + transport mechanism changes from a diffusion‐controlled vehicular transport of small Li + complexes to hopping‐type ion transport through the exchange of anions in the Li + ‐containing aggregate species . This must be true to explain the exceptional performance of the Li/LMR cell employing the DEMEFTFSI 0.6 LiFTFSI 0.4 at high rates, despite its substantially lower conductivity and higher viscosity than the electrolytes containing 10 and 20 mol % LiFTSFI.…”
Section: Resultsmentioning
confidence: 99%
“…However, the formation of aggregate species seems to have a rather different influence on the transport of Li + ions. It has been proposed that, in a concentrated electrolyte, the Li + transport mechanism changes from a diffusion‐controlled vehicular transport of small Li + complexes to hopping‐type ion transport through the exchange of anions in the Li + ‐containing aggregate species . This must be true to explain the exceptional performance of the Li/LMR cell employing the DEMEFTFSI 0.6 LiFTFSI 0.4 at high rates, despite its substantially lower conductivity and higher viscosity than the electrolytes containing 10 and 20 mol % LiFTSFI.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the vehicular ion conduction mechanism observed in glyme-based systems, the ionic conduction through the silica particulate obstacles may be less restricted via the ion hopping conduction mechanism in the SL-based MLSs. 22,23 Furthermore, we studied the effects of the presence of silica particles on the lithium transference number (t Li+ ) via the electrochemical polarization method using a Li/Li symmetric cell. 32,33 However, there was no significant difference in the t Li+ values between the MLSs and the composites, as indicated by the t Li+ of 0.048 and 0.047 for [Li(G3)][TFSA] and the silica composite (V silica = 0.025), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Aerosil 200 (supplied by Nippon Aerosil, with a primary particle diameter of approximately 12 nm) was used as the silica nanoparticle; it was dried for 24 h in a vacuum oven at 120°C prior to use. The samples were prepared gravimetrically, and the volume fractions were calculated from the bulk density values of fumed silica (2.2 g cm ¹3 ) and 13,22,23 Suspensions of the silica particles in the MLSs with a volume fraction of the silica particles (V silica ) were prepared using a conditioning mixer (AR-250, THINKY) by mechanical mixing for 20 min to ensure homogeneous mixing, followed by degassing for 3 min to remove the air bubbles from the samples. The composites did not undergo any phase transitions within the range of room temperature to 80°C.…”
Section: Methodsmentioning
confidence: 99%
“…83 Watanabe showed that the highly concentrated SL-LiTFSI supports higher rates of the Li-S cell cycling compared to concentrated ethers due to higher t + of the SL-based electrolytes discussed above while suppressing polysulfide dissolution, especially when a localized concentrated electrolyte concept is applied by mixing SL-LiTFSI with the highly fluorinated ether. 100 This approach can also be viewed as an extension of the sparingly solvated approach to limit polysulfide dissolution. 101 An interesting twist of Li-sulfur chemistry was reported by Yang et al, who realized that, although the cathodic stability limit of WiSE cannot directly accommodate Limetal, it can do so with sulfur.…”
Section: Beyond Li-ion Chemistries Sodium-ion Batteriesmentioning
confidence: 99%